Analysis of the relationship between job enthusiasm,learning enjoyment with job autonomy and organizationa‌l trust by mediating role of performance appraisal - Rahime pourheydar; Maryam Samery; mohammad hassani; Nilofar Mortazanejad (پژوهش در نظام‌های آموزشی, 2023)
The growth and development of any country depends on its education and teachers are an important factor affecting this progress.. This research was an applied research in terms of the aim and regarding data collection was correlation. The data analysis method is path analysis type.The statistical population were all senior high-school teachers in Urmia city that between them 306 teachers were selected as research sample by utilizing Morgan table and proportionate stratified random sampling technique. Tools of this research included researcher-made questionnaire for appraisal the performance of teachers)Pourheydar&etal,1398), job enthusiasm (Schaufeli&Baker,2003), organizational trust (Skut & Rader,2003)‌and learning enjoyment (pekran,2005), job autonomy(Fridman,1999). The content validity, confirmatory and exploratory factor analysis for validity of instrument were tested, and confirmed. Reliability of instruments were confirmed by Cronbach’s alpha test. According to findings tested model is fitness. Mediating role of teachers performance appraisal in relationship between learning enjoyment, job enthusiasm with job autonomy and organizationa‌l trust was confirmed. In order to creat‌e learning enjoyment in students and job enthusiasm in teachers we can develop teachers job autonomy and creat‌e a climate of trust in the school while accurately appraisal their performance.